BALINESE LOCAL WISDOM IN WELLNESS TOURISM: A STUDY OF TRADITIONAL HEALING PRACTICES IN UBUD - Bagus Angga Wiguna, I Gusti; Suwarnata Triana, Dwik (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
Ubud, Bali has evolved into one of the leading destinations in the wellness tourism sector by promoting traditional healing practices rooted in Balinese local wisdom. This study aims to examine how traditional healing methods such as usadha (herbal and spiritual medicine based on lontar manuscripts), melukat (spiritual purification rituals using holy water), tapak dara (energy-balancing therapy), and the role of balian (traditional healers) contribute to the development of authentic and sustainable wellness tourism. The research employs a descriptive qualitative method, using field observations and online document analysis, including official websites of traditional healing service providers. The findings indicate that these healing practices offer not only holistic health benefits but also serve as a medium for preserving Balinese culture and spirituality. Despite the risk of commodification, most practitioners remain committed to maintaining the sacred and authentic values of these traditions. This study confirms that wellness tourism in Ubud can develop sustainably through an approach that emphasizes cultural integrity and spiritual depth.